Ruptured Suprarenal Abdominal Aortic Pseudoaneurysm with Superior Mesenteric and Celiac Arteries Occlusion, Revealing Behçet’s Disease: A Case Report - Rashaideh, Mohammed A. (Vasc Specialist Int, 2019)
Behçet’s disease (BD) is a multisystemic, chronic autoimmune inflammatory vasculitic disease with an unknown etiology. Although the literature reports that vascular involvement occurs in 7% to 38% of all BD cases, the arteries are rarely involved; however, arterial involvement is usually associated with significant mortality and morbidity. We report the case of a young female patient who presented to the emergency department with severe abdominal pain and a history of weight loss. The patient was evaluated using computed tomography angiography, which revealed a ruptured suprarenal aortic pseudoaneurysm with occlusion of both the superior mesenteric and celiac arteries. Urgent surgery was performed with aortic repair with an interposition graft and superior mesenteric artery embolectomy. The patient’s clinical history and radiological imaging findings were strongly suggestive of the diagnosis of BD with vascular involvement.